2007
DOI: 10.1002/cvde.200606517
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Doped Spinel Cobalt Oxide Thin Films and Evaluation of their Thermal Stability

Abstract: Spinel cobalt oxide doped with nickel and zinc are deposited using a CVD reactor equipped with a pulsed spray evaporation system. This process allows easy control of the film composition through the adjustment of the composition of the liquid feedstock; a linear dependence is observed in both cases. Doped spinels with atomic ratios of doping-metal to Co ranging from 0 to 0.5 are deposited and subjected to various surface characterization methods. Zinc as a doping metal, which nonselectively occupies the octahe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Be- yond 600 • C, there is a progressive loss of crystallinity resulted from the broadening of the spinel bands. At 650 • C, the spinel gradually releases its oxygen lattice to form CoO, with the characteristic band in the range of 700−800 cm −1 , demonstrating that Co 3 O 4 can be thermally stable at 650 • C. CoO is the only phase observed above 700 • C. These thermal stability limits fit well with earlier observations on mixed oxides with Co 3 O 4 as one of the limiting systems [34].…”
Section: B Thermal Stabilitysupporting
confidence: 87%
“…Be- yond 600 • C, there is a progressive loss of crystallinity resulted from the broadening of the spinel bands. At 650 • C, the spinel gradually releases its oxygen lattice to form CoO, with the characteristic band in the range of 700−800 cm −1 , demonstrating that Co 3 O 4 can be thermally stable at 650 • C. CoO is the only phase observed above 700 • C. These thermal stability limits fit well with earlier observations on mixed oxides with Co 3 O 4 as one of the limiting systems [34].…”
Section: B Thermal Stabilitysupporting
confidence: 87%
“…Noble metals such as, Ag, Au, Pt and Pd have been reported to enhance sensor response and selectivity . Addition of Ni and Zn as a dopant in Co 3 O 4 increases the electrical conductivity and decreases resistivity . However, the application of Zn doped Co 3 O 4 material has been scarcely reported in glucose detection application.…”
Section: Introductionmentioning
confidence: 99%
“…e results also showed that Au nanoparticles enhance the reaction kinetics at low temperature. In addition, Bahlawane et al [15] indicated that the addition of nickel or zinc affects the conductivity of Co 3 O 4 , generating metal vacancies and decreasing resistivity. Similar results for the addition of SnO 2 to Co 3 O 4 sensor materials were reported [16].…”
Section: Introductionmentioning
confidence: 99%